2021
DOI: 10.3390/cancers13205034
|View full text |Cite
|
Sign up to set email alerts
|

Reinspection of a Clinical Proteomics Tumor Analysis Consortium (CPTAC) Dataset with Cloud Computing Reveals Abundant Post-Translational Modifications and Protein Sequence Variants

Abstract: The Clinical Proteomic Tumor Analysis Consortium (CPTAC) has provided some of the most in-depth analyses of the phenotypes of human tumors ever constructed. Today, the majority of proteomic data analysis is still performed using software housed on desktop computers which limits the number of sequence variants and post-translational modifications that can be considered. The original CPTAC studies limited the search for PTMs to only samples that were chemically enriched for those modified peptides. Similarly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Therefore, it is imperative to understand the molecular mechanism by which GBM occurs and to establish a direct and clear treatment strategy [ 45 ]. Studies have shown that the BCAS1 gene is greatly amplified on the chromosomes of some cancer patients, but whether and how BCAS1 is involved in the development of cancer are unclear [ 32 ]. Dysregulation of the mRNA alternative splicing mechanism of eukaryotic cells, which results in abnormal gene expression or products, is known to be involved in the development of many diseases, especially cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is imperative to understand the molecular mechanism by which GBM occurs and to establish a direct and clear treatment strategy [ 45 ]. Studies have shown that the BCAS1 gene is greatly amplified on the chromosomes of some cancer patients, but whether and how BCAS1 is involved in the development of cancer are unclear [ 32 ]. Dysregulation of the mRNA alternative splicing mechanism of eukaryotic cells, which results in abnormal gene expression or products, is known to be involved in the development of many diseases, especially cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cheung et al analyzed exon expression arrays in patients with GBM and found that BCAS1 undergoes alternative splicing modification [ 26 ]. In addition, using the Clinical Proteomics Tumor Analysis Consortium (CPTAC) dataset, Prakash et al also found that the BCAS1 protein sequence significantly changed in GBM [ 32 ]. This aroused our interest in the relationship between alternative splicing of BCAS1 and the establishment of GBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Clinical Proteomic Tumor Analysis Consortium (CPTAC) 97–99 initiated by NCI focuses on understanding the molecular basis of cancers including viral cancers with the help of proteomic techniques. Particularly, mass spectrometry is used by CPTAC to analyze the cancer samples for identification and quantification of protein constituents and perform phosphorylation.…”
Section: Cancer Related Databases and Toolsmentioning
confidence: 99%
“…Likewise, software designed for use on the Cloud have been demonstrated but have been slow to be adopted despite the promise of improved speed and increased biological relevance processing on the Cloud can allow. 10,11 One method to circumvent the size of the generated LCMS files is to apply pre-filters to remove tandem mass spectra (MS2) that are of interest. We have recently described Reporter Ion Data Analysis Reduction (RIDAR) which allows us to set minimum quality filters and relative quantification values in isobarically tagged proteomic datasets.…”
Section: Introductionmentioning
confidence: 99%